Programa educativo de natación para mejorar el estado psicobiológico del adulto mayor en el centro integral del adulto mayor municipio de San Juan Bautista 2019 - Rengifo García, Julio (2022)
This research has been raised as a problem: What is the effect of the educational swimming program on the improvement of the psychobiological status of the elderly at the Comprehensive Center for the Elderly in the district of San Juan Bautista, province of Maynas, Loreto region, 2019? The objective was: To evaluate the effect of the educational swimming program on the improvement of the psychobiological state of the elderly at the Comprehensive Center for the Elderly in the district of San Juan Bautista, province of Maynas, Loreto region, 2019. The research was evaluative with Quasi-experimental design of a single group with pre and post test. The analysis of the results, through the Student's t-test for related samples, concludes that there is a significant difference for both anxiety and depression since the significances were less than 0.05; p = 0.000 (p < 0.05), which indicates that the levels of anxiety and depression were significantly reduced thanks to the application of the educational swimming program. The analysis of the results of the biological state, through the application of the Student's t-test for related samples, concludes that the significance values of the body mass index, heart rate and blood pressure were less than 0.05; p = 0.000 (p < 0.05); that is, the application of the program had significant effects on the improvement of the biological state of the elderly in the study sample.